A strategic approach to multistakeholder negotiations - Edmunds, D.; Wollenberg, Eva Karoline (2001)
Environment and development practitioners increasingly are interested in identifying methods, institutional arrangements and policy environments that promote negotiations among natural resource stakeholders leading to collective action and, it is hoped, sustainable resource management. Yet the implications of negotiations for disadvantaged groups of people are seldom critically examined. We draw attention to such implications by examining different theoretical foundations for multistakeholder negotiations and linking these to practical problems for disadvantaged groups. We argue that negotiations based on an unhealthy combination of communicate rationality and liberal pluralism, which underplays or seeks to neutralize differences among stakeholders, poses considerable risks for disadvantages groups. We suggest that negotiations influenced by radical pluralist and feminist post-structuralist thought, which emphasize strategic behaviour and selective alliance-building, promise better outcomes for disadvantaged groups in most cases, particularly on the scale and in the historical contexts in which negotiations over forest management usually take place.